Ultra low power mixer with out-of-band RF energy harvesting for wireless sensor networks applications (Engineering Review, 2020)
An ultra low power mixer with out-of-band radio frequency (RF) energy harvesting suitable for the wireless sensors network (WSN) application is proposed in this paper. The presented mixer is able to harvest the out-of-band RF energy and keep it working in ultra low power condition and extend the battery life of the WSN. The mixer is designed and simulated with Global Foundries ’ 0.18 ? m CMOS RF process, and it operates at 2.4GHz industrial, scientific, and medical (ISM) band. The Cadence IC Design Tools post-layout simulation results demonstrate that the proposed mixer consumes 248 ? W from a 1V supply voltage. Furthermore, the power consumption can be reduced to 120.8 ? W by the out-of-band RF energy harvesting rectifier